History Education and Conflict Transformation Social Psychological Theories, History Teaching and Reconciliation - Psaltis, Charis; Carretero, Mario; Čehajić-Clancy, Sabina (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book is open access under a CC BY 4.0 license. This volume discusses the effects, models and implications of history teaching in relation to conflict transformation and reconciliation from a social-psychological perspective. Bringing together a mix of established and young researchers and academics, from the fields of psychology, education, and history, the book provides an in-depth exploration of the role of historical narratives, history teaching, history textbooks and the work of civil society organizations in post-conflict societies undergoing reconciliation processes, and reflects on the state of the art at both the international and regional level. As well as dealing with the question of the 'perpetrator-victim' dynamic, the book also focuses on the particular context of transition in and out of cold war in Eastern Europe and the post-conflict settings of Northern Ireland, Israel and Palestine and Cyprus. It is also exploring the pedagogical classroom practices of history teaching and a critical comparison of various possible approaches taken in educational praxis. The book will make compelling reading for students and researchers of education, history, sociology, peace and conflict studies and psychology.